Injury prevention of elite wheelchair racing athletes using simulation approaches - Lewis, A. R.; Phillips, E. J.; Robertson, W. S. P.; Grimshaw, P. N.; Portus, M. (Proceedings, 2018)
A high prevalence of shoulder injuries exists across the wheelchair using populations. To maintain competitive longevity and optimise performance, athletes must employ techniques which pose minimal injury risk. A computational model was used to assess relationships between the magnitude of reaction moments at the shoulder with key propulsion characteristics, including; contact and release angles, hand speed at contact, and joint angles at contact. Subject-specific musculoskeletal models (mass, maximum isometric force) for two elite wheelchair racing athletes were derived, and driven through kinetic and kinematic data obtained using motion capture. Greater reaction moments (min 72.6 Nm, max: 1077.8 Nm) at the shoulder were correlated with hand velocity (7.2 m/s-9.3 m/s) at contact (|r| > 0.866, p < 0.013), push time (|r| > 0.866, p < 0.013), and kinematic positioning at contact (|r| > 0.784, p < 0.020). Variations between athlete reaction force at the pushrim and joint reaction moments demonstrate the importance of coupled kinematic and modelling analysis in prescribing technique adaptations.